Signaling Crosstalk of TGF-β/ALK5 and PAR2/PAR1: A Complex Regulatory Network Controlling Fibrosis and Cancer - Ungefroren, Hendrik (Int J Mol Sci, 2018)
Both signaling by transforming growth factor-β (TGF-β) and agonists of the G Protein-coupled receptors proteinase-activated receptor-1 (PAR1) and -2 (PAR2) have been linked to tissue fibrosis and cancer. Intriguingly, TGF-β and PAR signaling either converge on the regulation of certain matrix genes overexpressed in these pathologies or display mutual regulation of their signaling components, which is mediated in part through sphingosine kinases and sphingosine-1-phosphate and indicative of an intimate signaling crosstalk between the two pathways. In the first part of this review, we summarize the various regulatory interactions that have been discovered so far according to the organ/tissue in which they were described. In the second part, we highlight the types of signaling crosstalk between TGF-β on the one hand and PAR2/PAR1 on the other hand. Both ligand–receptor systems interact at various levels and by several mechanisms including mutual regulation of ligand–ligand, ligand–receptor, and receptor–receptor at the transcriptional, post-transcriptional, and receptor transactivation levels. These mutual interactions between PAR2/PAR1 and TGF-β signaling components eventually result in feed-forward loops/vicious cycles of matrix deposition and malignant traits that exacerbate fibrosis and oncogenesis, respectively. Given the crucial role of PAR2 and PAR1 in controlling TGF-β receptor activation, signaling, TGF-β synthesis and bioactivation, combining PAR inhibitors with TGF-β blocking agents may turn out to be more efficient than targeting TGF-β alone in alleviating unwanted TGF-β-dependent responses but retaining the beneficial ones.